Faktor-faktor Penyusunan Laporan Keuangan pada Pelaku UMKM Berdasarkan SAK EMKM di Kecamatan Buleleng - Amanda, Kadek Koni; Julianto, I Putu; Vijaya, Diota Prameswari (Universitas Pendidikan Ganesha, 2025)
This research was conducted with the aim of knowing the factors that influence the preparation of financial reports by MSME actors based on SAK EMKM in Buleleng District. The theory used in this study is the entity theory. The method used in this research is a quantitative research method with primary data being used. The population in this study comprises all registered and operational Micro, Small, and Medium Enterprises (MSMEs) in Buleleng District, totaling 2,639 MSMEs. The sample was determined using the Slovin formula, resulting in a total of 190 MSMEs, and determined using the Simple Random Sampling method. Data processing utilized SPSS version 27.0 for Windows. Based on the research results, it shows that each variable, background education (X1), accounting understanding (X2), and SAK EMKM socialization (X3) has a positive effect on the preparation of financial reports based on SAK EMKM (Y). This may mean that the overall variables used can influence MSME actors in preparing financial reports based on SAK EMKM.